(untitled) (Journal of Asian Development Studies, 2020)
Spiritual intelligence has been portrayed as an important contributor to an enhanced sense of meaning and purpose within workplace leadership. Despite a growing body of literature significant gaps remain, particularly in understanding how spiritual intelligence is experienced and practiced by women leaders from non-Western countries. To address this gap, we set out to better understand how women academic leaders integrate spiritual intelligence practices within higher education environments. Phenomenological inquiry was used as a method of study. The findings generated two main approaches of integrating and assimilating spiritual intelligence into leadership practice: 1) To work with purpose and meaning; and 2) fostering and demonstrating shared values. We conclude that spiritual intelligence can serve as a way to transform the workplace into being more meaningful and purposeful by creating ‘spiritual’ – i.e. balanced and harmonious – relationships between and within employees.